Modeling on 137Cs Radioactive Dispersion in Gosong Coast as The Candidate Location for Nuclear Power Plant - Akhmad Tri Prasetyo; Muslim Muslim; Heny Suseno (Universitas Diponegoro, 2021)
The study of radioactive dispersion in the ocean should be conducted to prepare the construction of nuclear power plant (NPP) in Gosong Coast, West Kalimantan. This study estimated the distribution of 137Cs radioactive from various scenarios of radioactive waste dumping if nuclear emergency is occurred during NPP’s operation. These scenarios were distinguished based on their volume discharges of radioactive waste into the ocean, included 10 m3 (Scenario I), 50 m3 (Scenario II), and 100 m3 (Scenario III). Model dispersions were constructed for 15 days by Delft3D-Flow module. The simulation showed that ocean current directions were not significantly different among spring and neap tide, instead the ocean current during the spring period dominantly increased rather than neap period. Ocean currents at Gosong Coast flowed parallel to the shoreline towards Singkawang Coastal Area during ebb tide. Meanwhile, during flood tide, ocean currents at Gosong Coast flowed offshore through Burung Archipelagic. The dispersed model showed the distribution of 137Cs radioactive for 15 days reaching to coastal areas of Burung Archipelagic, Singkawang, and Southern Sambas Coast. Each scenario of the disposal system did not influence the marine pollution of the West Kalimantan Sea.